Trust Based Security for Cognitive Radio Networks - Parvin, Sazia; Han, Song; Hussain, Farookh Khadeer; Al Faruque, M. (ACM, 2010)
With the rapid increase of wireless applications, Cognitive Radio (CR) has been considered as a promising concept to improve the utilization of limited radio spectrum resources for future wireless communications and mobile computing. Because of the dynamic behavior of Cognitive Radio Networks (CRNs), secure communication in CRNs becomes more critical than for other conventional Wireless networks. So, in this paper we propose a trust-based security solution for CRNs. Trust is calculated from the requesting node depending on various communication attributes and the evaluated trust is compared with the trust threshold value. Depending on the resultant decision, the requested service is available to the requesting user. We prove the security of our proposed scheme in terms of security analysis.